To solve the equation \((x−1)(2x+5)=0\) using the Zero Product Property, we set each factor equal to zero:
- \(x - 1 = 0\)
- \(2x + 5 = 0\)
For the first equation: \[ x - 1 = 0 \implies x = 1 \]
For the second equation: \[ 2x + 5 = 0 \implies 2x = -5 \implies x = -\frac{5}{2} \]
Thus, the values of \(x\) that make the quadratic equation equal to zero are \(x = 1\) and \(x = -\frac{5}{2}\).
So the correct response is: The quadratic equation will equal zero when \(x\) equals negative \(\frac{5}{2}\) and \(x\) equals 1.